Identification of single nucleotide polymorphism c.957A>C of PLAG1 gene and its association with growth traits in Bali cattle - Putra, I. G. R.; Sari, D. A.; Rachmawati, S. M.; Oktaviani, R.; Noor, R. R.; Jakaria, J. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The PLAG1 gene is one of the genes that affect the growth traits located on chromosome 14 in cattle. This study aims to obtain SNP of the PLAG1 gene in exon 1 and exon 2 and their association with growth traits in Bali cattle. The number of samples used was 52 samples of Bali cattle, 10 samples of Peranakan Ongole (PO), and 8 samples of Limousine cattle. Identification of SNPs PLAG1 gene was analyzed by direct sequencing method and genotyping of selected SNPs was carried out using PCR-RFLP. Association of genotypes of SNP c.957A>C with growth using t-test. There were 7 SNPs in exon 2 of the PLAG1 gene, namely SNP c.339A>G, c.489C>T, c.795A>G, c.957A>C, c.1023C>T, c.1056A>G, and c.1353A>G. SNP c.957A>C was validated by PCR-RFLP using TaqI enzyme and obtained three genotypes, namely genotypes AA, AC, and CC with allele frequency A and C, respec-tively 0.10 and 0.90 in Bali cattle, while in PO and Limousine cattle were monomorphic. Genotype association of SNP c.957A>C PLAG1 gene were not associated with birth weight (BW0), weaning weight at 205 days of age (WW205), yearling weight at 365 days of age (YW365), yearling weight at 730 days of age (YW730), and average daily gain (ADG). SNP c.957A>C as a specific SNP for Bali cattle needs to be investigated in further research as a candidate marker for growth traits in Bali cattle.